Social life of jeans in Yugoslavia - Kolanović, Maša (2012)
The paper is posing a questions what was the use of jeans in everyday life and popular culture in Yugoslav socialism, what was the difference from its use in the Western culture and were there any differences from its use in the countries of the Eastern block? The main thesis of the paper implies that the dominant meaning of jeans as a symbol of the global popular culture, freedom, casualness, the American lifestyle, resistance to forms, rules, and high culture etc. had its specific life in Yugoslav socialism which dynamically changed during the last three decades of Yugoslavia.